SISI GELAP DARI RETURN SAHAM DI PASAR MODAL INDONESIA: LIKUIDITAS, DAN RISIKO SISTEMATIS - Laynita Sari; Rio Nardo (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
The COVID-19 outbreak has had a serious impact on investment activities in Indonesia. One of the aspects of concern in the midst of the coronavirus outbreak is the decrease in investor interest in capital market activities in Indonesia. Therefore, it can be predicted that there is a potential decrease in the level of profit (return) that will be received by shareholders. The purpose of this study is to investigate the influence of liquidity and systematic risks on returns. The analysis tool used to test the influence between panel variables is the analysis of panel data regression. The findings of this study are that liquidation has no significant effect on the return of company shares. In addition, the second finding proves that systematic risk has a positive and significant effect on the return of the company's shares. Our findings are reinforced by the results of robustness test statistically, which confirms that companies that have a high beta value, then the return of the company's shares will tend to be high.